Putting migration in context: a review of how theory and methods shape climate-induced migration research findings - Turner, Matthew; Rice, Anika M.; Fornof, Emily; Ribot, Jesse (Frontiers in Climate, 2025)
Widespread media reports that climate change is driving international migration have led to an upsurge in research seeking to verify this phenomenon. In a methodological review of this research, we identified close to 3,000 studies referring to climate-induced emigration from Mesoamerica and West Africa and found only 102 that empirically evaluate the causal link. We analyze the causal inference implications of these 102 studies’ methodological characteristics and how these are shaped by conceptual framing, data sources, and region. Cluster analysis identified three groups of studies based on conceptual framing–45 largely ignoring and 33 fully engaging with the context of migration decisions and vulnerabilities of those exposed to climate change, with 24 in between. Studies were also coded for how they incorporated key methodological features needed to support causal claims. We find that conceptual framings, choice of data, and data availability in each study region strongly influence the prevalence of basic causal inference problems (e.g., mismatched spatial and temporal scales, over-aggregation of migration data, lumping of destination types). A key feature of ‘decontextual’ studies is an over-reliance on weather-migration correlation. These approaches neglect the causal nexus surrounding migration, which involves many factors beyond those attached to weather but which may co-vary in certain instances. Such analyses are prone to spurious correlations and fail to address the specifics of who migrates in the face of climate change and why.